THE EFFECT OF PROJECT-BASED LEARNING ON FIFTH-GRADE STUDENTS’ IPAS LEARNING OUTCOMES: A QUASI-EXPERIMENTAL STUDY - Husnu Mubarak; Azizah Azizah; Sri Wahyuni; Sinta Satria Dewi Pendit; Wirdana Wirdana (Jurnal Visipena, 2025)
The learning model greatly determines the effectiveness of learning, One of the learning models that can be applied to overcome problems is to use the Project Based Learning learning model which provides opportunities for students to learn actively. The purpose of this study is to determine the Effect of the Use of Project Based Learning on the Learning Outcomes of Grade V Students of SD Inpres Bumi Sagu. This study is an experimental research conducted on two groups, namely the experimental group and the control group. The research design used in this study is Quasi Experimental Design using a Non-equivalent Control Group Design. The population in this study is grade V students of SD Inpres Bumi Sagu, which totals 30 students. The samples in this study were class VB as the control class and class VA as the experimental class. The research instruments are in the form of pretest and posttest. Data were analyzed using the SPSS 30.0-assisted Independent Sample t-Test. The results of the analysis showed a significance value (p-value) of 0.001 < 0.05 which means that there is a significant difference between the two groups. These findings show that Project Based Learning is effective in improving student learning outcomes. Theoretically, this research strengthens the theory of constructivism in learning, while it can practically be an alternative to innovative learning models in elementary schools.